Pengaruh Komunikasi, Motivasi, dan Kedisiplinan terhadap Prestasi Belajar Mahasiswa - Sunarsih Sunarsih; Desvira Zain; Sulaiman Sulaiman (Jurusan Akuntansi Politeknik Negeri Pontianak, 2021)
This study aims to determine the effect of communication, motivation and discipline on student learning achievement majoring in business administration. In this study, the sample was 88 people from a population of 750 people who were taken randomly, using regression analysis. Sources of data obtained are primary data and secondary data. With a quantitative approach. Data collection techniques through interview techniques, observation and documentation. The data analysis technique is by means of assumption test, descriptive analysis and statistical analysis with linear regression using the help of SPSS (Social Sciences Program Statistics) version 22.0. From the research that has been done, it shows that communication, motivation and discipline on student achievement of majoring in business administration have a significant effect. Communication, motivation and discipline influence student achievement so that educators / lecturers continue to improve student readiness in the learning process so that they can be maximized so as to improve student achievement. The potential of students must continue to be developed so that it becomes a complete achievement.